1983
DOI: 10.1056/nejm198308253090802
|View full text |Cite
|
Sign up to set email alerts
|

Homocystinuria — The Effects of Betaine in the Treatment of Patients Not Responsive to Pyridoxine

Abstract: The treatment of homocystinuria that is not responsive to pyridoxine is not usually biochemically or clinically successful, and vascular, ocular, and skeletal complications commonly supervene. Persistent marked homocysteinemia appears to be the most important biochemical disturbance leading to these complications. Ten patients with cystathionine beta-synthase deficiency that was not responsive to pyridoxine and one patient with homocystinuria due to a defect in cobalamin metabolism were treated with 6 g daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(91 citation statements)
references
References 13 publications
1
89
0
1
Order By: Relevance
“…Supplementation with betaine, starting at 3 g twice a day, is experimental and has yielded conflicting results, but can be used in very highrisk patients. 79,80 Once the patient is within goal range, a fasting tHcy can be repeated on a yearly basis. 9…”
Section: Suggestions For Current Homocysteine Screening and Managementmentioning
confidence: 99%
“…Supplementation with betaine, starting at 3 g twice a day, is experimental and has yielded conflicting results, but can be used in very highrisk patients. 79,80 Once the patient is within goal range, a fasting tHcy can be repeated on a yearly basis. 9…”
Section: Suggestions For Current Homocysteine Screening and Managementmentioning
confidence: 99%
“…In humans, there is little safety data regarding the use of betaine in healthy individuals. In hyperhomocysteinemic patients, betaine is used to lower plasma homocysteine concentrations (Wilcken et al, 1983;Singh et al, 2004), which is suggested to be an independent risk factor for coronary heart disease (El-Khairy et al, 1999;Chambers et al, 2000;Humphrey et al, 2008). Hyperhomocysteinemia is also associated with hyperinsulinemia and insulin resistance, which in turn increases the risk of cardiovascular diseases (Meigs et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Wilcken et al reported on the effects of betaine supplementation (6 g per day) in 10 patients with pyridoxine-nonresponsive HCU in conjunction with pyridoxine (100 mg/day) and folic acid (5 mg/day). 21 Six of these patients were also on a protein-restricted diet. All of these patients showed a substantial reduction in total free Hcy as a consequence of betaine supplementation with the average plasma level dropping from 57 µmol/L prior to treatment to 6 µmol/L during treatment.…”
Section: Betainementioning
confidence: 99%
“…The average decrease in plasma Hcy concentration is reported to be between 74% and 92% following doses of 6-20 g day −1 of betaine. 42,43 However, some studies have found no clinical benefit using 6 g day A number of limited trials have been performed to investigate these aspects of betaine therapy, but these have typically been limited by relatively short study durations and/or the use of normal volunteers rather than HCU patients who are likely to have different responses to the application of betaine. [45][46][47] Some investigators have tried to model the effects of HCU for studying betaine dosing by using a methionine-loading strategy but again, the time course of this kind of analysis is not suitable for detecting possible metabolic adaption induced in long-term betaine therapy.…”
Section: Optimal Dosage and Timing Of Betaine Treatment In Hcumentioning
confidence: 99%